A study of the chlorine-aluminium interface - Gudrun A. Saevarsdotti (The Minerals, Metals and Materials Society, 1996)
For decades tile aluminium industry has been practicing gas treatment of aluminium melts. This treatment is of great importance because of its influence on 'impurity" and inclusion removal from the melt. The gas-melt interaction is greatly influenced by the gas composition, melt temperature etc. This paper gives an overview of the interaction between argon-chlorine gas mixtures and the aluminium melt. It covers the thermodynamics of the reaction between the chlorine and a number of different elements commonly found in liquid aluminium, and discusses the behaviour of reaction products in the melt. The paper reports an experimental study of the behaviour of the chlorine-molten aluminium interface, using sodium contaminated aluminium melt with and without the addition of grain refiner.